Welcome aboard future civil engineer / Ts. Noraziyan Abd Aziz and Ts. Hafizah Muhamad Azlan - Abd Aziz, Noraziyan; Muhamad Azlan, Hafizah (Unit Penerbitan FKAPP, 2021)
Welcome! Welcome! Welcome! A special welcome to new students and a welcome back to all students in the School for Civil Engineering at UiTMCPP. As in the previous semester, a special briefing session for all students was organised by the Academic Advisor Unit (AAU). The session has continued after the pandemic and is now held as an online event. The first briefing session was held on October 8th, 2021, for all new students of CEEC110 and CEEC221 using the Microsoft Teams platform. This session started at 9.00 am and was emceed by Nur Syahirah Binti Othman, a representative from the Penang Civil Engineering Students Society (PCES). The first semester students were given a warm and hearty welcomed by Dr. Haji Anas bin Ibrahim (Head of School for Civil Engineering), Ts. Dr. Muhamad Faizal Pakir Mohamed (Coordinator of CEEC221), and En. Mohd Zaini Bin Endut (Coordinator of CEEC110).